The analyses of the stress resilience concepts’ in the world psychology (The Journal of Psychology and Sociology, 2020)
This paper aims to make an analyses and systemization oб /им f stress resilience concepts in the framework of world psychology. Authors begin with the defining the role of stress in humans’ life re- ferring to the dual nature of the stress. On the one hand as a power that trigger humans’ development and survivance, on the other hand as a power that can destroy humans. The second nature of the stress emphasizes the necessity to cope with it in order to thrive. The ability to cope was referred to the stress resilience ability. Authors analyzed and systemized Russian, Kazakhstani, and the far-abroad countries’ concepts of stress resilience. The concepts include both theoretical and experimental world studies of such scientists as Avdulova  T.P., Dyakov S.I., Tashimova  F.S., Mynabyeva A.K., Garmezy, Luthar, Zi-   gler, Gest, Reed, Masten, and others. The analyses starts from the history of stress resilience studies that primarily were revealed in the literature about schizophrenia. Then early studies of patients with severe disorders focused primarily on understanding maladaptive behavior, and a subgroup of patients with relatively adaptive models that was considered as atypical for them and thus, paved the way to study this atypical behavior as an ability to confront the stress. Authors focused on drawing up a holistic under- standing of stress resilience phenomena referring to the world concepts and explaining the mechanisms and main factors of stress resilience. As a summary and referring to the abovementioned concepts this paper offers the definition of stress resilience and a holistic understanding of mechanism and factors of stress resilience.Key words: stress, coping, resilience, adaptation, pdychological health.